Heterogeneity of Triple‐Negative Breast Cancer: Differences in Clinicopathologic and Ultrasound Features Between Premenopausal and Postmenopausal Patients. (18th November 2019) - Zhu, Kai; Wang, Dongmo; Li, Ziyao; Du, Guoqing; Guo, Qiang; Wu, Tong; Li, Juan
Abstract : Objectives: The aim of this study was to determine whether any salient differences exist in triple‐negative breast cancer (TNBC) between premenopausal and postmenopausal patients by comprehensively comparing the ultrasound (US) and clinicopathologic features of these patients. Methods: A detailed evaluation of the US and clinicopathologic features of 60 tumors from 60 patients with a diagnosis of TNBC (36 premenopausal and 24 postmenopausal women) was conducted in this retrospective study. Results: Triple‐negative breast cancer in premenopausal patients was more likely to show a round or oval shape and microlobulated margins, more commonly exerted effects on surrounding tissue, and showed grade 3 blood flow according to the method of Adler et al ( Ultrasound Med Biol 1990; 16:553–559) compared with tumors in postmenopausal women. Triple‐negative breast cancer in postmenopausal patients showed some similar US features as those observed in estrogen receptor–positive tumors, including irregular shapes, angular or spiculated margins, and nonparallel growth to the skin ( P < .05 for all). Conclusions: Although US cannot be used to unequivocally identify TNBC, it can distinguish some salient US features regarding TNBC between premenopausal and postmenopausal women. Such information can then provide some valuable predictive information on the diagnosis of TNBC for clinicians.